PENGEMBANGAN APLIKASI BIMBINGAN TUGAS AKHIR MAHASISWA BERBASIS WEBSITE PADA PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR FKIP UNIVERSITAS RIAU - Eddy Noviana; Otang Kurniaman; Muhammad Nailul Huda (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
This research is research of application development of final project of student based on website at Prodi PGSD FKIPUniversitas Riau by using waterfall model. The formulation of the problem in this research are: (1) how the design ofdeveloping the final project application of student based on the website of Prodi PGSD FKIP Universitas Riau? and (2)whether the program designed to assist the final project guidance on Prodi PGSD FKIP University of Riau ?. The purpose ofthis research is (1) to design a system that can assist the process of guidance of final assignment of students to Prodi PGSDFKIP Universitas Riau and (2) to know the response about the use of application of final student task based on the website ofProdi PGSD FKIP Universitas Riau. This research is a development research with waterfall model. Development stage isdone in four stages, namely: (1) stage study of literature; (2) needs analysis phase; (3) application design; and (4)application testing phase and conclusion. The result of the research stated that the application of the final assignment of thestudents based on the website of PGSD Study Program of FKIP Universitas Riau is valid with four references, namely: (1)correctness aspect (truth); (2) reliability (reliability) aspect; (3) integrity; and (4) usability (usage). Based on the results ofeffectiveness test on the students obtained data that the application of the final project-based student guidance websiteincluded in the category of very effective average percentage is 84.89% with very effective category. It is marked by theacquisition: 1) the correctness (truth) of 84.93% with very effective category; 2) reliability (reliability) of 86.37% with veryeffective category; 3) integrity (integration) equal to 86,08% with very effective category; and 4) usability (usage) of 82.17%with very effective category. The average percentage is 84.89% with very effective category. So it can be concluded that theapplication development of final student task based on the website Prodi PGSD FKIP University of Riau has been declaredeffective and has been widely used.